KETAHANAN ALAMI JENIS-JENIS BAMBU YANG TUMBUH DI INDONESIA TERHADAP RAYAP TANAH (Coptotermes curvignathus Holmgren) - Jasni; Ratih Damayanti; Rohmah Pari (BRIN Publishing, 2017)
Natural durability of each bamboo species is different, thus information on natural durability of bamboo species is important for its utilization. This paper investigates the natural resistance of bamboo species against subterranean termites as a basis for species classification. Twenty species of bamboo from various regions in Indonesia (West Java, Banten, the Central of Java, Lampung and Bogor Botanical Garden) were tested against subterranean termites Coptotermes curvignathus Holmgren according to SNI 7204-2014. Parameters observed were weight loss percentage of bamboo, survival rate of the termites and degree of attack (subjectively). Results showed that based on the weight loss, three bamboo species could be grouped into resistance class I, five species into class II, three species into class III, seven species as class IV and two species as class V. Based on the survival rate of the termites, one of the bamboo species was classified in class I, four species in class II, one species in class III, 11 species in class IV, and three species in class V. Furthermore, according to the degree of attack, four species were heavily damaged, while 16 species showed moderately damage. From the result, it can be concluded that one species of bamboo namely apus (Gigantochloa apus) has the highest resistance class (class I), and four other species of bamboo namely hitam (G. atroviolacea), kuring (G. kuring), india/tulda (Bambusa tulda) and lemang (Schizostachyum brachycladum), were classified in resistance class II. In the utlization, the five species of bamboo can be used without preservation, while the remaining 15 species of bamboo in resistance class III V should be preserved before using.